Image Enhancement in Wavelet Domain Using Histogram Equalization and Median Filters (International Journal of Innovative Research in Computer Science & Technology, 2023)
Image enhancement is one of the  challenging but crucial methods that is employed in image  processing technology for enhancing the visual appearance  of images. This paper presents an effective and efficient  image enhancement model in which Non Local mean (NLM)  filter is used along with Minimum Mean Brightness Error Bi Histogram Equalization (MMBEBHE) and Brightness  Preserving Dynamic Fuzzy Histogram Equalization  (BPDFHE) techniques. The primary objective of the  proposed image enhancement model is to enhance the quality  of images by reducing the noise effect in them. To do so, we  have selected four different images of Barbara, camera, Lena  and Hand whose quality is increased and analyzed on three  different noise levels of 15, 20 and 25 respectively. Here, we  have used NLM filter which is an advanced filtration  technique for denoising the images. Also, MMBEBHE and  BPDFHE techniques have been implemented for enhancing  the quality of images on different noise levels. The efficiency  and usefulness of proposed image enhancement model is  examined and validated in MATLAB software under Mean  Square Error (MSE) and Peak to Signal Ratio (PSNR)  values.
Keywords: Image enhancement; Histogram; Median Filters; NLM; MMBEBHE; BPDFHE